2019
DOI: 10.1021/acsbiomaterials.9b00810
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar Potassium Inhibits Myofibroblast Conversion and Reduces Scar Tissue Formation

Abstract: Scar formation is a natural result of almost all wound healing in adult mammals. Unfortunately, scarring disrupts normal tissue function and can cause significant physical and psychological distress. In addition to improving surgical techniques to limit scar formation, several therapies are under development toward the same goal. Many of these treatments aim to disrupt transforming growth factor β1 (TGFβ1) signaling, as this is a critical control point for fibroblast differentiation into myofibroblasts; a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Furthermore, these signals are co-localized with the total cell nuclei, demonstrating the presence of fibroblasts cells in the cultures obtained from keloids tissues (Figure 2F,L) and from perilesional tissues (Figure 3F,L). Moreover, it is known that myofibroblasts are typically found in fibrotic skin tissues such as keloids [29,30]. Thus, we evaluated the presence of myofibroblasts, revealed by the anti-alpha-smooth muscle actin (α-SMA) antibody, in cell cultures isolated from keloid tissue or perilesional tissue.…”
Section: Characterization Of Cell Cultures Isolated From Keloid and P...mentioning
confidence: 99%
“…Furthermore, these signals are co-localized with the total cell nuclei, demonstrating the presence of fibroblasts cells in the cultures obtained from keloids tissues (Figure 2F,L) and from perilesional tissues (Figure 3F,L). Moreover, it is known that myofibroblasts are typically found in fibrotic skin tissues such as keloids [29,30]. Thus, we evaluated the presence of myofibroblasts, revealed by the anti-alpha-smooth muscle actin (α-SMA) antibody, in cell cultures isolated from keloid tissue or perilesional tissue.…”
Section: Characterization Of Cell Cultures Isolated From Keloid and P...mentioning
confidence: 99%
“…The BG coating produced an appreciable K, Sr, and B release due to the BG coating dissolution. These inorganic ions have been reported to readily facilitate the accessibility of new vessels for bone formation and within an accepted dosage level (K, 0–320 mmol/L; Sr, 0.1–24 mmol/L; B, 0–1000 ng/mL). It was also worth mentioning that the Biogel modification influenced the mass decrease in the first week, probably attributing to the more dissolution of the Biogel.…”
Section: Resultsmentioning
confidence: 99%
“…In this aspect, the CSi-Mg10/BG also exhibited the most intensive angiogenesis cycles and the longest duration. It is evident that the vasogenic and osteogenic effects of CSi-Mg10/BG might be related to the release of high concentrations of K, Sr, and B ions. , Therefore, the finely tuned surface modification can also induce new vessel growth. The physicochemical properties of the scaffold surface are considered another important factor on the biocompatibility of biomaterials .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Ca is the second most abundant element in ALI. It has been reported that low concentrations of extracellular potassium may accelerate and favor fibroblast differentiation, thus forming scar tissue [ 43 ]. Low intracellular K + concentrations favor interleukin-8 expression, which plays an important role in stimulating re-epithelialization, migration and proliferation of dermal cells during wound healing [ 26 ].…”
Section: Discussionmentioning
confidence: 99%